A further new genus of Drepanicinae (Neuroptera: Mantispidae) from the earliest Eocene Fur Formation, Denmark - Makarkin, Vladimir N.; Nielsen, Christian; Perkovsky, Evgeny E. (Zootaxa, 2025)
Protheristria roldae gen. et sp. nov. (Neuroptera: Mantispidae: Drepanicinae) is described from the earliest Eocene Fur Formation, Denmark. This is the second genus of Mantispidae and Drepanicinae from this formation. The new genus is distinguished from other drepanicine genera by a combination of fore- and hind wing venation character states: one gradate series of crossveins is present in the radial to intramedial spaces; pterostigma is short and pale; Sc distally (bordering the pterostigma) is very pale; all branches of RP are forked once. The two genera known from the Fur Formation, Danomantispa Makarkin et al., 2025 and Protheristria gen. nov., are not closely related and certainly belong to different genus groups.